Urban rooftop-nesting Common Nighthawk chicks tolerate high temperatures by hyperthermia with relatively low rates of evaporative water loss. Issue 3 (18th May 2021) - Newberry, Gretchen N; O′Connor, Ryan S; Swanson, David L
Abstract: Heat tolerance for many birds under climate and land use change scenarios could be compromised in the future. Common Nighthawks ( Chordeiles minor ) belong to the Caprimulgiformes, a generally heat-tolerant order, but few studies have assessed heat tolerance in Caprimulgiform chicks, which might be particularly susceptible to heat stress. In the midwestern United States, nighthawks primarily nest on flat graveled rooftops in urban areas, as natural nesting habitats are limited. Urban rooftop-nesting nighthawks are likely exposed to higher environmental temperatures than birds nesting at more thermally buffered natural sites, and evaporative cooling might be impeded by the typically high summer humidity in their Midwest breeding range. This combination of heat and humidity might negatively impact heat tolerance of nighthawk chicks. We exposed 7- to 14-day-old nighthawk chicks ( n = 15) from rooftop nests to ambient temperatures (Ta s) up to 51°C and at typical summer dew points. Chicks initiated gular flutter at a mean ambient temperature of 42.4 ± 3.4°C (mean ± SE). Evaporative water loss (EWL) rates increased significantly with increasing temperature above 44.0 ± 1.5°C. Chicks showed little evidence of lower and upper bounds of the thermal neutral zone over the range of temperatures (30–44°C) for which we measured oxygen consumption. Body mass loss was significantly positively correlated with temperature during heat exposure trials. Chicks tolerated Ta s up to 51°C and body temperatures (Tb s) up to 48°C, which, along with the high temperatures at which gular flutter and high rates of EWL were initiated, suggest that nighthawk chicks are tolerant of high ambient temperatures, even with relatively high humidity. Given the high rates of mass loss and high Tb s at hot ambient temperatures, chick heat tolerance mechanisms could be detrimental for rooftop-nesting nighthawks given projected increasing trends for both heat and humidity in the midwestern United States. Lay Summary: Climate and land use trends may interact to stress physiological capacities for avian heat tolerance. Common Nighthawks belong to the heat-tolerant nightjar order and, in the midwestern United States, nest almost exclusively on hot and humid urban rooftops. We exposed 7- to 14-day-old chicks to laboratory conditions simulating their rooftop thermal environment and measured rates of oxygen consumption, evaporative water loss (EWL), and body temperature (Tb ). Chicks survived ambient temperatures up to 51°C and Tb s up to 48°C with comparable rates of EWL under heat exposure to adults but EWL resulted in body mass loss. Chicks were hyperthermic under heat exposure, suggesting that increases in Tb help reduce EWL. Thermoregulation under hot, humid conditions, which are projected to increase in the future, might precipitate a decline in urban nighthawk populations, despite their capacity for heat tolerance.